Voorheen en thans. - Lievevrouw-Coopman, M.; Doudelet, Karel (Gent : Vanderpoorten, 1901)
Bibliotheek E. Anseele
Dedicator: Lievevrouw-Coopman M., dedicatee: Anseele, Edward (sr.)
Nederlands
Monografie